Antibacterial Effects of Essential Oils on P. aeruginosa, Methicillin-Resistant S. aureus, and Staphylococcus spp. Isolated from Dog Wounds - Sezener Kabay, Merve Gizem; Inal, Sinem; Gökmen, Sedat; Ergüden, Volkan Enes; Fındık, Arzu; Güvenç, Tolga; Kayhan, Hülya; Güvenç, Dilek (MDPI AG, 2024)
Background: Essential oils exhibit several biological activities such as antimicrobial, antioxidant, proliferative, and anti-inflammatory. This study was aimed at investigating the antimicrobial effects and cytotoxic activities of niaouli, palmarosa, and clove essential oils. Methods: Content analyses of these essential oils were carried out by gas chromatography–mass spectrometry. The antibacterial activity was screened against methicillin-resistant S. aureus ATCC 43300, P. aeruginosa ATCC 27853, P. aeruginosa PAO1, S. aureus ATCC 25923, and 44 isolates (22 P. aeruginosa isolates, 4 S. aureus isolates, and 18 Staphylococcus spp. isolates) obtained from dogs with previous wound infections who were included in the current study. The antimicrobial effects of essential oils were investigated using disk diffusion and minimum inhibition/bactericidal concentration methods. Additionally, the antibiofilm, protease, elastase, and gelatinase activities of the essential oils were evaluated. Different concentrations of each essential oil ranging from 10 to 1000 µg/mL were also analyzed in terms of cell viability by WST-8 assay in primary canine fibroblast cells. Results: The fibroblast cell viabilities of palmarosa, niaouli, and clove oils at a 1000 µg/mL concentration were 75.4%, 96.39%, and 75.34%, respectively. All the EOs were found to have bactericidal effects with MBCs/MICs of 0.015 to 0.5 µL/mL against P. aeruginosa, Staphylococcus isolates (p < 0.001). Palmarosa was found to have the largest inhibition zone diameter (20.5 ± 6.6, 16.4 ± 2.3) compared to other essential oils in the disk diffusion test against Staphylococcus spp. and P. aeruginosa (p < 0.001). But none of the EOs reduced protease, elastase, and gelatinase activities, which are some of the virulence properties of the tested bacteria. Conclusions: These results showed that palmarosa, niaouli, and clove essential oils act as potential antibacterial agents for dogs against P. aeruginosa, methicillin-resistant S. aureus, and Staphylococcus spp., without damaging the skin.
Keywords: RS1-441; primary fibroblast cells; Pharmacy and materia medica; R; Medicine; antibacterial effects; antibiofilm effect; essential oils; Article